PENGARUH KEPEMIMPINAN DAN KINERJA DOSEN TERHADAP MUTU PELAYANAN DI POLITEKNIK NEGERI BATAM - Hati, Shinta Wahyu (IQTISHODUNA, 2013)
In general education at the college level to prioritize quality of service as the primary goal, becausethe quality of service quality is a major factor to demonstrate the performance of the organization will be thedesire and commitment of stakeholders. This study aims to analyze the influence of leadership on employeeperformance and its effect on the quality of service. Object of this study is its staff Polytechnic Batam, RiauIsland. The samples were 50 employees lecturer. Data were collected using a questionnaire. The findings ofthis study indicate that the value of R square is 0.681. Shows the value of effective leadership and facultyperformance is quite good, will raise the quality of service at the Polytechnic of 68.1%. Subsequent researchfindings employee performance variables lecturer dominant influence on the quality of service quality inBatam Polytechnic of 55.9%